(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
River water is a natural resource that is a necessity for living things, but until now there has been a lot of pollution caused by industrial activities. Kundur river water pollution occurs because the disposal of industrial waste that is managed ineffectively and the river becomes a place for accumulation of waste disposal from all human activities, causing pollutants to enter the river before finally being channeled into the sea or lake, and at a certain point when the river’s capacity for If the pollution load has reached its limit, what will happen is river pollution. So we need a way that can reduce this pollution by using various adsorbents, one of which is activated carbon from rice husks and banana peels. The aims of the study were to determine the quality of activated carbon from rice husks and kepok banana peels with different weight variations, to determine the effect of the effectiveness of activated carbon from rice husks and kepok banana peels, to determine the decrease in levels of heavy metals iron (Fe), TSS and pH, after Adsorption was carried out with activated carbon from rice husks and adsorption with activated carbon from kepok banana peels. This research was conducted by preparing raw materials, carbonization, activation, and absorption of river water content with activated carbon. The results showed that activated carbon of kepok banana peels with a concentration of 20% H3PO4 could reduce iron (Fe) levels from an initial value of 0.52 mg/L to 0.00 mg/L, TSS levels decreased from an initial value of 180.3 to 0.46 mg. /L., and the pH of the acid solution from the initial value of 5.4 to neutral with a value of 7.2. The conclusion is that the activated carbon of banana peel kepok is better than rice husk activated carbon to reduce the content of heavy metal iron (Fe), TSS and neutralize pH.